Analysis of Physical Activity Motives in Sports Communities in the City of Bandung - Bunga Putri Septiyani; Adang Suherman; Jajat (Universitas Negeri Semarang, 2026)
Physical Activity has an important role in maintaining the health and quality of life of the community. One form of physical activity participation that is developing in urban areas is through sports communities. This study aims to analyze the motives for physical activity in members of the sports community in the city of Bandung. The study used a quantitative approach with a cross-sectional observational design. The research sample was from 90 respondents who were active members of the running, swimming, and calisthenics communities in the city of Bandung. The instrument used is the Indonesian version of the Motives for Physical Activity Measure-revised (MPAM-R) questionnaire which has been tested for reliability. Data analysis was carried out descriptively and the One-Way ANOVA test. The results of the study show that the motive for physical activity of members of the sports community is in the good category in all dimensions of MPAM-R. The ANOVA test showed that there was no significant difference in the motive for physical activity between sports communities (p >0.05). These findings indicate that the type of exercise is the main factor in shaping the motivation to engage in physical activity, but the community environment, exercise experience, and individual awareness of the benefits of physical activity have a more dominant role. Thus, the sports community can be an effective means in encouraging participation and sustainable physical activity of the community.